2004
DOI: 10.1128/aem.70.5.2685-2691.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enterotoxigenic Clostridium perfringens Type A Isolates in American Retail Foods

Abstract: Currently there is only limited understanding of the reservoirs for Clostridium perfringens type A food poisoning. A recent survey (Y.-T. Lin and R. Labbe, Appl. Environ. Microbiol. 69:1642-1646, 2003) of nonoutbreak American retail foods did not identify the presence of a single C. perfringens isolate carrying the enterotoxin gene (cpe) necessary for causing food poisoning. The present study revisited this issue, using revised methodology and food sampling strategies. In our survey, cpe-positive C. perfringen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
3
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 18 publications
9
125
3
2
Order By: Relevance
“…In another study, 37% of the meat and poultry samples were detected as positive for C. perfringens but different from our results 17% of the isolates were carrying cpe gene (27). Similarly Wen and McClane (2004) reported that 56 of 147 (38%) chicken meat were contaminated with C. perfringens and only one isolate was positive for cpe.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In another study, 37% of the meat and poultry samples were detected as positive for C. perfringens but different from our results 17% of the isolates were carrying cpe gene (27). Similarly Wen and McClane (2004) reported that 56 of 147 (38%) chicken meat were contaminated with C. perfringens and only one isolate was positive for cpe.…”
Section: Discussioncontrasting
confidence: 47%
“…Epidemiological studies showed that more than 90% of C. perfringens outbreaks were associated with only meat and poultry products. (14,25,27,32). In various studies type A was reported to be the dominant type of C. perfringens isolated in poultry diseases (especially in necrotic enteritis) and from industry, processing line, products and environment worldwide (6,17,21,32).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, although C. perfringens was detected in 142 of 200 samples (beef, chicken, and pork), only two from beef and one from chicken were cpe-positive [26]. In another study of 887 food samples, 278 were positive for C. perfringens but only 10 were also cpe-positive [27]. The type A strain of C. perfringens was detected in 22 of 180 turkey meat samples and most were cpe-negative [28].…”
Section: Discussionmentioning
confidence: 99%
“…Diluted meat samples (1 ml) were inoculated into FTM broth and the tubes were incubated for 24 h at 37°C in an anaerobic jar HP-11 (Oxoid, Hampshire, UK) containing AnaeroGen TM Sacchet AN35 (Oxoid, Hampshire, UK) (Wen and McClane 2004). Enrichment culture (0.1 ml) thus obtained was spread over the tryptose sulfite cycloserine (TSC) agar (Himedia Labs, Mumbai, India) plates using a sterile glass rod and incubated anaerobically for 24 h at 37°C.…”
Section: Enrichment and Cultivationmentioning
confidence: 99%